Silica-based versus silica-titania sol–gel materials – comparison of the physical properties: surface tension, gelation time, refractive index and optical transmittance - Ulatowska-Jarża, Agnieszka; Hołowacz, Iwona; Wysocka, Katarzyna; Podbielska, Halina (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
Knowledge of the physical parameters and optical constants of sols and sol–gel materials is important in view of their possible applications. In this work, silica and silica-titania sols were examined. Gelation time, surface tension, refractive index and optical transmittance were measured. The sol–gel materials were produced from the silica precursor Si(OC2H5)4 mixed with the titanium dioxide precursor Ti(OC2H5)4 and 96% ethyl alcohol. It was stated that the surface tension of pure silica sols is much higher than in case of silica-titania sols. The refractive index of fresh samples is lower than of stored sols. The transmittance is highest for the fresh samples and it decreases with gelation time; however, this effect is stronger for silica-titania materials. By manipulating with the solvent content and titania addition, the required refractive index may be obtained.
Optica Applicata, Vol. 39, 2009, nr 1, s. 211-220
Keywords: optyka; silica-titania sol–gel materials; surface tension; gelation time; refractive index; optical transmittance